Integration of Ergonomic Intervention and Motor Control Exercises to Improve Work Posture and Reduce Musculoskeletal Complaints in Stone Crusher Workers - Wicaksono, Utomo; Prayogo, Dadan; Rachman, Aulia (Universitas Muhammadiyah Surakarta, 2025)
Introduction: The incidence of musculoskeletal disorders in industrial workers who rely on manual material handling was found to be 100%. Uncontrolled exposure to risk factors in the workplace will cause the cumulative effect of repetitive strain injury so that musculoskeletal disorders become progressive and chronic and have the potential to cause disability, drug abuse, absenteeism, and cost expenditure. This study aimed to examine the effect of integrating ergonomic interventions and motor control exercises to improve work posture and reduce musculoskeletal disorders in stone crusher workers. Methods: This study was a randomized controlled trial design with two groups, a control group, and a treatment group. The study respondents were selected randomly, each group consisting of 21 respondents. The control group intervention consisted of conventional physiotherapy actions: Portable Transcutaneous Electrical Nerve Stimulation (TENS) treatment modalities, Portable Ultrasound (US), passive joint mobilization, and passive stretching. The treatment group intervention is called the ergo movement system which consists of the stages of risk assessment, risk control-task adaptation, and motor exercise. The data assessed included work posture assessment using the Rapid Entire Body Assessment (REBA) instrument and musculoskeletal complaints using the Nordic Body Map instrument. Data measurements were conducted before the intervention and 4 weeks after the intervention. Results: The control group intervention statistically only had a significant impact on reducing musculoskeletal complaints 0.01<0.05 but had no impact on improving work posture 0.83>0.05. Meanwhile, the treatment group intervention significantly affected improving work posture 0.01<0.05 and reducing musculoskeletal complaints 0.01<0.05. Conclusion: The ergo movement system intervention was significantly more effective than conventional physiotherapy intervention in overcoming problems related to occupational health.